An evolutionary analysis of the volunteer's dilemma - Myatt, D; Wallace, C (University of Oxford, 2006)
The volunteer's dilemma is an asymmetric n-player binary-action game in which a public good is provided if and only if at least one player volunteers, and consequently bears some private cost. So long as the value generated for every player exceeds this private cost there are n pure-strategy Nash equilibria in each of which a single player volunteers. Quantal-response strategy revisions allow play to move between the different equilibria. A complete characterisation of long-run play as strategy revisions approximate best replies provides an equilibrium selection device. The volunteer need not be the lowest-cost player: relatively high-cost, but nonetheless stable players may instead provide the public good. The cost of provision is (weakly) reduced when higher values are associated with lower costs.